Bromodomain‐containing protein 4 and its role in cardiovascular diseases. Issue 7 (20th December 2020) - Li, Liang; Xie, Wei; Gui, Yu; Zheng, Xi‐Long
Abstract: Bromodomain‐containing protein 4 (BRD4), a chromatin‐binding protein, is involved in the development of various tumors. Recent evidence suggests that BRD4 also plays a significant role in cardiovascular diseases, such as ischemic heart disease, hypertension, and cardiac hypertrophy. This review summarizes the roles of BRD4 as a potential regulator of various pathophysiological processes in cardiovascular diseases, implicating that BRD4 may be a new therapeutic target for cardiovascular diseases in the future. Abstract : This review summarizes the roles of BRD4 as a potential regulator of various pathophysiological processes in cardiovascular diseases, implicating that BRD4 may be a new therapeutic target for cardiovascular diseases in the future.